2015
DOI: 10.1089/mab.2014.0068
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Med28 Specific Monoclonal Antibodies

Abstract: 1Med28 plays a role in transcription, signal transduction, and cell proliferation. The overexpression of med28 is associated with tumor progression in in vitro and in vivo models. Recently it has been reported that the elevated expression of med28 is associated with poor outcome in women with breast cancer. The expression level of med28 in in vitro and in vivo was examined by using anti-rabbit polyclonal antibody in previous reports. In this study, we report for the first time the generation and characterizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Specimens were ductal carcinoma between stage 1 and 2. Immunohistochemical staining was performed as described previously [ 48 ]. Sections (5 μm) were stained for 1 h at RT with anti-p53 and anti-ZNF224 antibodies diluted with 1/50.…”
Section: Methodsmentioning
confidence: 99%
“…Specimens were ductal carcinoma between stage 1 and 2. Immunohistochemical staining was performed as described previously [ 48 ]. Sections (5 μm) were stained for 1 h at RT with anti-p53 and anti-ZNF224 antibodies diluted with 1/50.…”
Section: Methodsmentioning
confidence: 99%
“…However, cancer genomics data, where MED28 was found to be amplified in various cancers, including breast cancer, ovarian cancer, pancreatic cancer, sarcoma, lung adenoma, prostate cancer, and melanoma, clearly indicate that the overexpression of MED28 is closely related to cancer progression (Supplementary Figure S4A). In addition, the analyses of RNA-seq data from various cancers suggest that the gene amplification of MED28 closely correlates with an increase in MED28 mRNA expression (Supplementary Figure S4B) [10,36,37].…”
Section: Discussionmentioning
confidence: 99%
“…Constructs expressing Flag-ZNF224 (12), Myc-MED28 (18), and 6x His-MED28 (18) were previously verified. HA-tagged N-terminus of ZNF224 construct was kindly provided by Dr. Constanzo (University of Naples Federico II, Naples, Italy).…”
Section: Methodsmentioning
confidence: 99%
“…Previously, it was shown that ZNF224 downregulates the transcription of p53 and p21, and that MED28 is localized to the cytosol and nucleus (12,18). In addition, it is known that ZNF224 primarily localizes to the nucleus and forms a punctate pattern (12).…”
Section: Nucleus-specific Interactions Of Znf224 With Med28mentioning
confidence: 99%